A Weighted Multi-Domain Spectral Penalty Method with Inhomogeneous Grid for Supersonic Injective Cavity Flows (Communications in Computational Physics, 2009)
In [J. Comput. Phys. 192(1), pp.325-354 (2003)], we have developed a multi-domain spectral method with stable and conservative penalty interface conditions forthe numerical simulation of supersonic reactive recessed cavity flows with homogeneous grid. In this work, the previously developed methodology is generalized toinhomogeneous grid to simulate the two dimensional supersonic injector-cavity system. Non-physical modes in the solution generated at the domain interfaces due to thespatial grid inhomogeneity are minimized using the new weighted multi-domain spectral penalty method. The proposed method yields accurate and stable solutions of theinjector-cavity system which agree well with experiments qualitatively. Through thedirect numerical simulation of the injector-cavity system using the weighted method,the geometric effect of the cavity wall on pressure fluctuations is investigated. It isshown that the recessed slanted cavity attenuates pressure fluctuations inside cavityenabling the cavity to act potentially as a stable flameholder for scramjet engine.